Influence of typical pretreatment on cotton stalk conversion activity and bio-oil property during low temperature (180–220 ℃) hydrothermal process. (15th November 2022) - Zhang, Libo; Yang, Xiao; Sheng, Yequan; Huang, Qiguang; Yang, Zhilin; Shi, Yang; Guo, Xuqiang; Ge, Shengbo
Graphical abstract: Highlights: Pretreatment could enhance cotton stalk (CS) hydrothermal conversion activity. CS surface microstructure changed by pretreatments benefits hydrothermal bio generation. The best bio-oil properties and CS conversion activity was realize by NaOH/EtOH pretreatment. Pretreatment could be used as an important way to regulate the composition of bio-oil. Abstract: Conversion of agricultural and forestry waste biomass into high value-added bio-oil by mild hydrothermal method is of great significance to reduce the diesel consumption and alleviate the shortage of high-quality fuel oil supply. Most of the current research focuses on the parameter adjustment in the hydrothermal process, including temperature, time, catalyst and cosolvent, but the influence of the structure of raw materials on the hydrothermal conversion activity and the properties of hydrothermal oil is less. In this study, several typical pretreatment methods (including ball milling, alkali + ball milling, urea/NaOH and NaOH + ethanol) were used to change the structural characteristics of agricultural waste cotton stalks (CS), and the treated CS were used for hydrothermal conversion at low temperature (180–220 ℃). Taking the yield of hydrothermal bio-oil as index, the results show that various pretreatment can effectively improve the hydrothermal conversion activity of CS, improve the combustion performance of hydrothermal bio-oil and adjust the composition of hydrothermal oil. The hydrothermal bio-oil obtained by NaOH + EtOH pretreatment has the best properties, the yield is 7.41 % (wt, 220 ℃, 2 h), the calorific value is 24.16 MJ/kg, and the energy recovery is 10.98 %, which is higher than untreated CS bio-oil (with yield of 3.90 wt% at 220 ℃ and 2 h, calorific value is 23.32 MJ/kg and energy recovery of 10.98 %). The research will strengthen the role of lignocellulosic raw material structure in the hydrothermal process, which will play an important role in promoting the industrialization process of hydrothermal technology in the field of biomass, especially considering the optimization of operating parameters of various raw materials in the future industrialization.